Gothenburg very early supported discharge: evaluating differences in costs and environmental impact due to rehabilitation consumption during the first year in patients hospitalized due to mild stroke - Lena Rafsten; Annie Palstam; Katharina S. Sunnerhagen (BMC Health Services Research)
Abstract Background It has been showed that Early Supported Discharge could decrease the length of hospital stay and thus a cost saving alternative to conventional in-hospital stroke rehabilitation. This might lead to decreased environmental impact due to reduced need of in-hospital care but has not been evaluated. Methods One hundred forty adult patients from a stroke unit at the Sahlgrenska University Hospital who were consecutively included in the GOTVED study and then randomized to Very Early Supported Discharge (VESD) group or to a control group who received ordinary discharge was included. Descriptive data are presented as mean ± standard deviation (SD) or median and interquartile range (IQR), as appropriate. The chi-square test or Mann-Whitney U test was used to test for group difference. A two-sided value of p ≤ 0.05 was considered to represent statistical significance. Results The VESD group had an average hospital stay that was 2 days shorter than that of the control group, resulting in a mean cost of € 11,151 in the VESD group, and for the control group € 10,741 (p = 68). The mean environmental impact in kg CO2 emissions was 525.3 (± 240.1) kg CO2/patient in the VESD group, VESD visits included, and 552.5 (± 284.2) kg CO2/patient in the control group (p = 0.55). Discussion Despite the fact that the 2-day difference in hospital stay between the VESD group and the control group was not statistically, if generalized a two days shorter in-hospital stay to all hospitalized stroke patients in Sweden, would results in a saving of € 6,944,500 /year. Two days shorter in-hospital days would also mean a reduction in CO2 emissions with approximately 360,050 CO2 kg /year. These hypothetical possible reductions in healthcare emissions would contribute to more sustainable healthcare. Conclusion A policy of offering more patients VESD after stroke could reduce healthcare costs and environmental impact, contributing to sustainable healthcare. Trial registration clinicaltrials.gov: NCT01622205, 2012-06-18 .